On the Geastrum species (Geastraceae, Basidiomycota) described by Rick - Trierveiler-Pereira, Larissa; Da Silveira, Rosa Mara B. (Phytotaxa, 2012)
Geastrum lloydianum, G. trichiferum and G. violaceum, described from Brazil by Johannes Rick at the beginning of the 20th century, are redescribed, lectotypified and compared with recent collections. Two recently described species, viz. G. hirsutum from Brazil and G. episcopale from Argentina, are regarded as synonyms to G. trichiferum and G. violaceum, respectively. Basidiomata are illustrated in color. SEM images show basidiospores, and line drawings show hyphae and basidia.